THEORETICAL FOUNDATION OF CHILDREN’S LITERATURE AND ITS VALUE FOR YOUNG GENERATION (Proceedings of International Educators Conference, 2024)
The article specifically focused on theoretical background of children's literature, its importance in the development and formation of children's personality in modern society, and analyzes the history of the emergence of children’s literature.